(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
The contemporary world hosts a complex network of social interactions that transcend physical boundaries and materialize in digital environments. In the context of the transformation and challenge of traditional identities, previously latent and socially unacceptable behaviors emerge. Using the Jungian concept of the “Shadow”, we investigate the phenomenon of cancel culture. In analytical psychology, the Shadow represents the part of the psyche that contains rejected, inadequate, or unwanted aspects of one’s personality. This study explored the relationship between the Shadow and cancel culture by examining tweets related to controversies in BBB 2021. The method employed involved collecting tweets over 6 weeks, followed by content analysis for data treatment. Simultaneously, a systematic analysis of the scenes that occurred was conducted, and data were subsequently cross-referenced. The results point to a high incidence of negative emotions, indicating a potential association with Shadow components. These were more elicited in the face of hostility and socially devalued behaviors, the so-called “dramas”. Cancellation occurred in parallel, indicating the association between the phenomena. This investigation highlights the importance of deepening the understanding of the dynamics of social media and its psychological aspects.